Prevalence of sexual dysfunction in married teachers of Nepal : A case study in Tikapur Municipality (Journal of Tikapur Multiple Campus, 2017)
Sexual dysfunction in male is alarming as the society has opened a bit in terms of sexual matter as sex education is provided in formal or informal level in our country. This paper mainly focuses on the prevalence of sexual dysfunctions viz. erectile dysfunction, premature ejaculation and loss of libido in the married teachers in Tikapur municipality area. Since the topic is very sensitive and needs privacy so judgmental sampling was carried out to choose the respondents and teachers of primary level to campus level were the population of the study. Total ten teachers were taken for the study. The age of respondents was forty years and over.The result was awakening in real sense. First the respondents were interested and co-operative while answer the questions and on the other hand there are many sexual dusfunctions among the respondents. All respondents were felt their sexual power was getting low at different stage. Majority of the respondents have at least one sexual problems though the most prevalent problem was erectile dysfunction at varying degree (mean 70 percent ) followed by premature ejaculation experienced by 60 percent of total respondents at varying degree.